The Effectiveness of the Realistic Mathematics Education (RME) Approach: The Role of Learning Models in Improving Students' Mathematical Problem-Solving Skills - Gustia Utami, Lianni; Turmudi,; Irwan, Ade (International Conference on Elementary Education, 2025)
This study aims to explore the effectiveness of the Realistic Mathematics Education (RME) approach in improving students' mathematical problem-solving skills, with a focus on flat and space figures. A quasi-experimental design with a nonequivalent control group was employed, involving purposive sampling to select class IVA as the experimental group and class VB as the control group, with each group consisting of 27 students. The data was collected through pre-tests and post-tests, which assessed the students' abilities in mathematical problem-solving. The study measured the change in performance before and after the intervention to evaluate the impact of the RME approach. The results indicated a significant improvement in the post-test scores of the experimental group, which received the RME intervention, with an average score of 85 compared to the control group's post-test score of 76. Furthermore, the experimental group showed a greater increase in scores, from an average of 64.59 in the pre-test to 85.89 in the post-test, while the control group increased from 63.85 to 76.19. These findings suggest that the RME approach was more effective in enhancing students' understanding of mathematical concepts and improving their problem-solving abilities. The study concludes that by making mathematics more contextual and relevant to real-world situations, RME can foster the development of critical problem-solving skills in students, offering valuable insights for teaching practices and curriculum development in mathematics education.